EVALUASI PENGGUNAAN ANTIBIOTIKA PADA INFEKSI KAKI DIABETIK (STUDI KASUS RAWAT JALAN DI POLIKLINIK ENDOKRINOLOGI RSUP Dr SARDJITO YOGYAKARTA) - , NINISITA SRI HADI; , Prof. Dr. Djoko Wahyono, SU, Apt ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Diabetic foot is common foot problems in persons with diabetes mellitus. It is ABSTRACT suggested that the prevalence of diabetic food cases increase along with the growing number of patients with diabetes mellitus. Diabetic foot commonly appears with manifestation of ulcers, infection, gangrene and Charcoat atrophy. Infection occurs in fifty percent of diabetic foot with ulcers that could lead to amputation if it is not immediately and appropriately treated. Proper antibiotics treatment prevents diabetic foot patient from amputation. This study aimed to understand the pattern of antibiotics usage amongst diabetic foot patients. The appropriateness of antibiotics therapy against current guideline was studied and compared with culture and sensitivity test results. Effectiveness of therapy and patientâs safety was then evaluated. Prospective cohort approach was used to this study. Data of diabetic foot patients was collected during November 2011 â January 2012 at Endocrinology Clinic of Sardjito Hospital. Collected variables included subject characteristics, antibiotics and other medication treatments, visual sign of diabetic foot infection and laboratory test results. Descriptive analysis was then conducted toward all variables. Majority of subjects obtain single therapy of antibiotic when diagnosed with diabetic foot infection (68,9%), where cefadroxil (43,3%) and ciprofloxacin (36,7%) are amongst the most prescribed. About 31% of antibiotics therapy was not appropriate with existing guideline. Culture and sensitivity tests strengthen this inappropriateness. It was found that 84.4% of antibiotics therapy was effective. However, there were 5,7% of antibiotic orders that potentially interact negatively with other medication during therapy.